The Subject: Challenges of the Digital - Elena O. Trufanova (Галактика медиа: журнал медиа исследований)
The article deals with the problem of the influence of digitalization processes on the concept of a subject. The purpose of the study is to analyze this influence and substantiate the possibility of preserving the category of the subject in the philosophical understanding of the present world and human being. It is shown that the expansion of human activity into the digital environment creates a situation in which the possibility of the existence of a subject as an integrity is questioned, since human activity is distributed across two environments — physical and digital. Several key problematic points are considered that make it necessary to clarify understanding of the subject in the modern world — these are the “disembodied” subject in the digital environment, the “decentralization” of the subject (i.e., the distribution of his activities in two different environments) and the alienation of information about the subject and messages belonging to it in the digital environment. It is revealed that at the heart of all these three problems, in one way or another, there is a gap between the bodily being of a person and its manifestations in the digital world, and it is demonstrated that the “incorporeality” of the subject in the digital world is illusory. It shows how a number of authors begin to use the concept of a “digital subject” to solve the above-mentioned problems and concludes that the use of such a term is possible only as a metaphor, since it hints at the existence of a certain separate entity in the digital world, whereas the subject cannot be considered in complete isolation from the physical environment. It is concluded that the distribution of human activity in the physical and digital environment is not the reason for the rejection of the concept of the subject. It is shown that the modern understanding of the subject is possible with a combination of approaches of body-oriented cognition and narrative approach, where the first is associated with the embodied being of the subject in the physical environment, and the second not only reflects the being of the subject in the digital environment, but also serves as a link between the digital and physical aspects of the subject. The combination of these two approaches allows us to preserve the idea of the integrity of the subject.